Does the Consumer Benefit from Price Instability?: Reply - Waugh, Frederick V. (Quarterly Journal of Economics, 1945)
Journal Article Does the Consumer Benefit from Price Instability? Reply Get access Fredebick V. Waugh Fredebick V. Waugh War Food Administration Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 59, Issue 2, February 1945, Pages 301–303, https://doi.org/10.2307/1884831 Published: 01 February 1945